SARME TECHNIQUE (SURGICALLY ASSISTED RAPID MAXILLARY EXPANSION): CLINICAL NEWS AND PERSPECTIVES - Iulia Chiscop; Norina Consuela Forna; Doriana Agop Forna; Sergiu Focsaneanu; Cristina Iordache; Cristian Budacu (Romanian Journal of Oral Rehabilitation)
Surgically assisted rapid maxillary expansion (SARME) is a widely accepted technique for managing transverse maxillary deficiency in adult patients, where conventional orthodontic methods are no longer effective due to skeletal maturation. This review explores the current understanding of SARME, focusing on anatomical and biomechanical principles, surgical protocols, orthodontic coordination, clinical outcomes, and comparative techniques. By disrupting resistant sutures through targeted osteotomies and applying controlled expansion forces via various appliances, SARME enables skeletal widening of the maxilla, resulting in improved arch form, occlusion, and nasal function. Tooth-borne, bone-borne, and hybrid devices are evaluated for their effectiveness in minimizing dental side effects and maximizing skeletal changes. The review also addresses complications such as relapse, asymmetry, and periodontal issues, emphasizing the importance of precise planning and interdisciplinary collaboration. Comparisons with MARPE and other expansion methods highlight SARME’s role in severe or complex cases. Ultimately, advancements in 3D imaging, digital planning, and customized devices are poised to usher in a future of safer, more efficient, and patient-specific interventions. SARME remains a cornerstone in the treatment of adult maxillary constriction, with ongoing innovation expanding its clinical potential.